2018
DOI: 10.1186/s12890-018-0649-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pulmonary function and peripheral vascular function in older Chinese: Guangzhou biobank cohort study-CVD

Abstract: BackgroundFindings describing the relationship between pulmonary function and peripheral vascular function have been inconclusive. We explored this relationship in Guangzhou Biobank Cohort Study-Cardiovascular Subcohort (GBCS-CVD).MethodsBrachial-ankle pulse wave velocity (baPWV) and ankle brachial index (ABI) were measured by a waveform analyser, and pulmonary function by turbine flowmeter spirometry. Predicted forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) were derived using equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…On the other hand, when the factors were analyzed as continuous variables, CAVI and carotid IMT were inversely associated with FVC%-predicted and FEV1%-predicted by multivariate regression analysis, compared to ABI being positively associated. Interestingly, where this could indicate that strong associations between parameters of vascular and pulmonary function are initiated in early-stage atherosclerosis among relatively young participants prior to the diagnosis of COPD, these results are consistent with a previous report investigating older participants by multivariate regression analysis 27 ) .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, when the factors were analyzed as continuous variables, CAVI and carotid IMT were inversely associated with FVC%-predicted and FEV1%-predicted by multivariate regression analysis, compared to ABI being positively associated. Interestingly, where this could indicate that strong associations between parameters of vascular and pulmonary function are initiated in early-stage atherosclerosis among relatively young participants prior to the diagnosis of COPD, these results are consistent with a previous report investigating older participants by multivariate regression analysis 27 ) .…”
Section: Discussionsupporting
confidence: 92%
“…The Caerphilly Prospective Study found lung function in mid-life to be a stronger predictor of arterial stiffness compared to later life in men [9]. A crosssectional association between arterial stiffness and reduced spirometry measures has also been found in general population studies where either c-f PWV or brachialankle PWV (ba-PWV) were found to be significantly and negatively associated with J o u r n a l P r e -p r o o f forced expiratory volume in 1 second (FEV 1 ) and forced vital capacity (FVC) [11][12][13].…”
mentioning
confidence: 71%
“…3 Brachial-ankle pulse wave velocity and ankle-brachial index were shown to be inversely and dose-dependently associated with arterial stiffness in a group of older Chinese subjects. 4 It was found that poorer lung function as shown by reduced FEV1 was strongly associated with arterial stiffness as indicated by carotid to femoral pulse wave velocity (cf-PWV) in a large group when followed up for approximately 5 years. 5 Hypertension was shown to be variably associated with poor lung function due to restriction as well as obstructive type.…”
Section: Introductionmentioning
confidence: 99%